FAKTOR PENGHAMBAT KEBIJAKAN FORMULASI TRADING IN INFLUENCE SEBAGAI KORUPSI DI INDONESIA - Sheryn Lawrencya; Ade Adhari (Fakultas Hukum Universitas Tarumanagara, 2021)
Trading Influence acts are non-mandatory offenses regulated in UNCAC and ratified by Law Number 7 of 2006 concerning UNCAC Ratification. Based on the cases that have occurred in Indonesia, the act of Trading Influence has actually developed in Indonesia, but is considered as “bribery”. Indonesia has not been able to ensnare the perpetrators of influence trading under the Corruption Law because there are no rules that regulate it, so there is legal uncertainty and a legal vacuum. This is due to the many factors that hinder the formulation of trading in influence policies in Indonesia. The research method used is normative using library materials or document studies for library research. This study looks back at what are the causes so that it is immediately regulated in Indonesia to be able to distinguish between bribery and the act of trading in influence in the context of overcoming corruption in Indonesia.